An Enhanced Debugger for Real-Time Fault Injection on Microprocessor Systems - Fidalgo, André Vaz (2017)
As electronic devices get smaller and more complex, dependability assurance is becoming fundamental for many mission critical computer based systems. This paper presents a case study on the possibility of using the on-chip debug infrastructures present in most current microprocessors to execute real time fault injection campaigns. The proposed methodology is based on a debugger, customized for fault injection and designed for maximum flexibility, and consists on injecting bit-flip type faults on memory elements without modifying or halting the target application. The proposed solution is easily portable and applicable to different architectures, providing a flexible and efficient mechanism for verifying and validating fault tolerant components.